Efficient Mechanisms for Public Goods with Use Exclusions - Norman, Peter (Review of Economic Studies, 2004)
Constrained efficient provision of an excludable public good is studied in a model where preferences are private information. The provision level is asymptotically deterministic, making it possible to approximate the optimal mechanism with a mechanism that provides a fixed quantity of the good and charges fixed user fees for access. In general, the fixed fees involve third degree price discrimination, but, if names are uninformative about preferences, the analysis provides a justification for average cost pricing.